Best Proximity Point for Some Type of Cyclic Mappingin Strong ḇ-Metric Space - Ali, Walaa Fadel; Ahmad, Buthainah A.A (Iraqi Journal of Science, 2025)
The best proximity point generalization of fixed point that is beneficial when the contraction map is not a self-map. The aim of this paper is to introduce new types of proximal contraction for cyclic mapping in strong ḇ-metric space that. Let  be complete strong ḇ-metric space and let  be two nonempty closed subsets of . Take the cyclic mapping  . If  is satisfies following condition   for all and , where  then  is Kannan cyclic, if  is satisfies following condition  for all  and , where  then  is Ćirić cyclic, if  is satisfies following condition  for all  and , where  Meir-Keeler mapping then  is Meir-Keeler -Kannan-Ghatterjee. The exi